Geomorphology of the continental shelf of Tavolara Island (Marine Protected Area 'Tavolara-Punta Coda Cavallo' – Sardinia NE). Issue 2 (3rd July 2019) - Deiana, Giacomo; Holon, Florian; Meleddu, Antonietta; Navone, Augusto; Orrù, Paolo E.; Paliaga, Enrico M.
ABSTRACT: In this document a geological – geomorphological map in scale 1: 25, 000 is presented. The study area is located inside the Protected Marine Area Tavolara – Punta Coda Cavallo, in north-eastern Sardinia. The study was done through integrated analysis of multibeam bathymetric and very high-resolution side scan sonar data, acquired in an area of 163 km 2 with the purpose of mapping the main biocoenoses and with particular reference to the coralligenous bioconstructions and the distribution of Posidonia oceanica. The interpretative hypotheses, based on the analysis of geophysical data, have been validated through diving surveys. This map represents a fundamental knowledge base and it constitutes an important technical-scientific support for long-term planning and management of the studied seabed.